VOLCANOSTRATIGRAPHY AND PETROGENESIS OF RAUNG VOLCANO, JEMBER AND BONDOWOSO AREA, EAST JAVA. - Sauqi Nur Sabila, Firman
Raung Volcano in Jember and Bondowoso, East Java, is an active volcano in Sunda Arc. There has never been any research that explain specifically about its tectonic environment. This research was done to determine the geological and tectonic setting of Raung Volcano using volcanostratigraphy and geochemical analysis. The methods in this research is remote sensing analysis and field observation to identify the geomorphology, stratigraphy, and geological structure. Petrographic observation and geochemical analysis using XRF (X-Ray Fluorescence) were used to identify the magmatic process and tectonic setting. Volcanostratigraphy of the research area is divided into four Crowns, those is Old Ijen Crown, Suket Crown, Gadung Crown, and Raung Crown. The Raung volcanism produces basalt, andesite, and pyroclastic breccia, which is divided into 19 rock units by source, lithology, and eruption period. The geological structure of the study area consisted of primary structures in the form of sheeting joint and autobreccia, and the secondary structure is Gadung Caldera Normal Fault, Raung Caldera Normal Fault, Kali Slincak Normal Fault and Kali Pace Strike-Slip Right-Lateral Fault. Minerals texture, anorthite content of plagioclase, crystal size distribution of plagioclase, geochemical data variation, and magma saturation analysis indicate magmatism process that occurs in the form of magma mixing, assimilation, and crystal fractionation. The analysis of phenocrist abundance and variations of geochemical data showing the magma series of Raung Volcano are included to (medium-high K) calc-alkaline series originated from convergent plate margin in subduction zone that forming volcanic-arc as an active continental margin feature.